2001
DOI: 10.1007/s003300101006
|View full text |Cite
|
Sign up to set email alerts
|

Clip placement facilitating the approach to breast lesions

Abstract: We describe a novel technique for marking non-palpable breast lesions with the aim of selecting the best approach prior to performing a biopsy. The technique employs a new coil, specifically designed for breast localization, guided by stereotaxy. This technique is reserved for selected cases in which the lesion is seen peripherally in only one mammographic view with negative or non-conclusive ultrasonographic results, and deeply seated after a stereotactic study. Once the coil is released beside the lesion, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Today, 125 I seeds are used most commonly in permanent implants for prostate cancer and are beginning to be used as permanent implants for breast cancer (Borchers et al 2004;Keller et al 2005). Over the past few years, several alternatives to the use of pre-operative wire localization for nonpalpable breast lesions have been investigated (Bergaz et al 2002;Li et al 2005). Some studies have focused on the use of 125 I seeds for more precise localization of lesions (Gray et al 2001(Gray et al , 2004Cox et al 2003;Hughes et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…Today, 125 I seeds are used most commonly in permanent implants for prostate cancer and are beginning to be used as permanent implants for breast cancer (Borchers et al 2004;Keller et al 2005). Over the past few years, several alternatives to the use of pre-operative wire localization for nonpalpable breast lesions have been investigated (Bergaz et al 2002;Li et al 2005). Some studies have focused on the use of 125 I seeds for more precise localization of lesions (Gray et al 2001(Gray et al , 2004Cox et al 2003;Hughes et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…A number of investigators have reported novel markers based on commercial products or alternative technology. Bergaz (2002) has reported on the use of a 3 mm stainless steel clip which is released with a specialized applicator and clearly visible by mammography. However, studies have indicated that these clips can migrate with time, limiting their accuracy for excisional biopsy purposes (Birdwell and Jackman 2003).…”
Section: Introductionmentioning
confidence: 99%